COMPARATIVE STUDY TO ASSESS THE EFFECTIVENESS OF NEBULIZED 3% HYPERTONIC SALINE AND NEBULIZED LEVOSALBUTAMOL IN THE MANAGEMENT OF BRONCHIOLITIS - SHIREEN, SARA; SULTANA, SAFURA; OMER, KHADIJA AKHTAR; QUTUB, ATIKA BEGUM; REDDY U, NARAYAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to compare the effects of nebulized 3% hypertonic saline and nebulized levosalbutamol in the management of bronchiolitis. Methods: Seventy children of age 1–24 months admitted into the hospital with the diagnosis of bronchiolitis. Participants were divided into two groups of 35 each. Group A was given nebulized 3% hypertonic saline and Group B was given nebulized levosalbutamol. Modified respiratory distress assessment instrument (RDAI) is used at admission, at 48 h after admission, and at the time of discharge to identify the reduction in scores between two groups. Results: The mean age of patients in the study population was 10.1±6.4 months. The mean birth weight of patients in Group A and Group B was 3.00±0.61 and 3.12±0.75. The percentage of male patients was 57.1% and the percentage of female patients was 42.8%. The modified RDAI score in Group A and Group B at admission, 48 h of admission, and at the time of discharge was 4.34±0.87, 2.4±1.03, and 0.67±0.05 (p=0.04) and 4.11±0.58, 3.60±1.00, and 2.51±0.96 (p=0.12). The hospital stay was observed to be lowered in Group A (3.77±0.88) compared to Group B (5.43±0.92; p=0.04). Conclusion: From the findings of our study, we conclude that nebulized 3% hypertonic saline, as it acts by hindering the pathophysiologic mechanism of bronchiolitis, is more effective in reducing the clinical severity score and length of hospital stay. Further 3% hypertonic saline also have the additional benefit of decreasing the economic burden of disease as it is safe, inexpensive, reduces the inpatient hospital charges by reducing the length of stay.